AN ANALYSIS ON THE IMPLEMENTATION OF THE HUMAN RESOUCES IN THE HEALTH FIELD PLANNING POLICY IN DEPOK, 2017 - Annadoroh, Hani; Ilyas, Yaslis (UI Scholars Hub, 2019)
According to the Minister of Health Regulation no. 33/2015 (Permenkes 33) on Guidelines for Composing the Human Resources in the Health Field (HRH) Planning, planning for HRH must be done from the bottom up. In 2016, Depok City has implemented the regulation, but the results were not applicable. This qualitative study analyzes the process of creating the planning document at Depok City in 2017 through in-depth interviews and documentary research. We discovered that the 2017 HRH planning document in Depok City did not completely follow all the steps stated in Permenkes 33. Ineffective communication caused lack of commitment and support from the stakeholders, which in turn, caused the lack of support from the bureaucratic structure, such as standard operational procedures, regulation, and allocation of resources, whether it was manpower, funding, or facilities. Therefore, we recommend that the socialization or advocation process to the stakeholders to be increased.